Hydrodynamic analysis of inland vessel self-propulsion for cargo transport for navigability in the Magdalena River. - Acosta Lopera, Oscar David Acosta (2019)
The subject of this study is the determination of the resistance of an inland vessel engaged in cargo transport in the lower course of the Magdalena River, considering that the hydrodynamic effects in shallow water navigation are very different compared to the effects in deep water navigation. The hydrodynamic analysis is realized numerically using Computational Fluid Dynamics (CFD). The Reynolds-Averaging Navier-Stokes equation (RANS) solver is applied to simulate viscous and pressure effects around a tank and a hull in confined tank considering the wall bottom and side effects in shallow water navigation. For turbulence effects, realizable k-? model is used. The motion of the vessel causes elevations of the free surface, in which, is captured using the Volume of Fluid method (VOF). For discretization of flow domain, the Finite Volume Method (FVM) is applied. The motion of the fluids is updated for each time step that allows the calculation of the resistance acting on the hull. The numerical simulation results are compared with experimental data obtained by the Technological Research Institute of the State of São Paulo (IPT, acronym in Portuguese) together with the existing empirical methods for this type of cases.